Urinary incontinence in women: treatment barriers and significance for Danish and German GPs. (23rd November 2019) - Elsner, Susanne; Juergensen, Martina; Faust, Elke; Niesel, Achim; Pedersen, Louise Schreiber; Rudnicki, Peter Martin; Waldmann, Annika
Abstract: Background: Female urinary incontinence (UI) is common. Only scant information exists on the significance of UI for GPs' consultations. Objectives: (i) To assess the significance of female UI for GPs and to look at barriers that could be detrimental to treatment by comparing GPs from Denmark and Germany, with different health systems and access to UI guidelines. (ii) To assess whether GPs' gender and age were relevant to the discussion of UI. Methods: We conducted a cross-sectional survey. In the Fehmarn belt-region, a Danish–German border region, a self-developed questionnaire was sent to all the GPs ( n = 930). Results: In total, 407 GPs returned the questionnaire (43%); 403 questionnaires were analysed. Using a scale from 0 (never) to 10 (always), addressing UI was reported with an average score of 3.8 (SD: 2.1) among Danish and 3.5 (SD: 2.1) among German GPs. The topic was discussed more frequently with female (4.2; SD 2.2) than with male GPs (3.2; SD 2.0). Danish GPs estimated the prevalence among their female patients at 10% (SD: 8.0) and German GPs at 14% (SD: 11.2). 61% of the Danish and 19% of the German GPs used UI guidelines. German GPs significantly more often reported the barrier 'uncertainty of how to treat UI' [OR = 5.39 (95% CI: 2.8; 10.4)]. Conclusions: In consultations with female GPs, UI was discussed significantly more frequently than with male GPs. Compared with the Danish GPs, German GPs stated significantly more uncertainties regarding UI treatment measures, and tended not to use UI guidelines.